Mercado dos prazeres : notas de uma etnografia multi situada em espaços de prostituição no interior de São Paulo - Pazzini, Domila do Prado (2015)
The prostitution is ambiguous: while it is recognized as an occupation is also a morally confusing activity to the dominant values at the same time that the state guarantees the occupancy condition for prostitute, criminalize the other activities in your surroundings (whose main implication is the operating profit of impossibility about the work of a prostitute) and victimizes. This injunction prostitution condition causes people dealing with this world end up creating conduct and internal codes of everyday action, so you can keep your active practices and markets, moving just between the spheres of legal and illegal, moral and immoral. This work aims to understand, from the codes and conducts the operation of some areas of prostitution in three different cities in the interior of São Paulo: Iris, Girassol and Gardenia. In each of these cities it was possible to see some prostitution contexts, especially in streets, squares and houses. These spaces was conducted fieldwork with interviews and analysis of media records (printed and virtual newspapers, blogs, brochures etc.).